A Structured Framework and Resources to Use to Get Your Medical Education Work Published - Su-Ting T. Li; Maryellen E. Gusic; Robert J. Vinci; Peter G. Szilagyi; Melissa D. Klein (Association of American Medical Colleges, 2018)
Introduction Medical educators often have great ideas for medical education scholarship but have difficulty converting their educational abstract or project into a published manuscript. Methods During this workshop, participants addressed common challenges in developing an educational manuscript. In small-group case scenarios, participants discovered the importance of the "So what?" in making the case for their project. Incorporating conceptual frameworks, participants chose appropriate outcome metrics, discussed how to frame the discussion section, and ensured appropriate journal fit. After each small-group exercise, large-group discussions allowed the small groups to report back so that facilitators could highlight and reinforce key learning points. At the conclusion of the workshop, participants left with a checklist for creating an educational manuscript and an additional resources document to assist them in avoiding common pitfalls when turning their educational abstract/project into a publishable manuscript. Results This workshop was presented in 2016 and 2017. Presenter evaluations were completed by 33 participants; 11 completed conference evaluations. The mean overall rating on presenter evaluations was 4.55 out of 5, while the conference evaluations mean was 3.73 out of 4. Comments provided on both evaluation tools highlighted the perceived effectiveness of the delivery and content. More than 50% of respondents stated that they planned to incorporate the use of conceptual frameworks in future work. Discussion This workshop helped participants address common challenges by providing opportunities for hands-on practice as well as tips and resources for use when submitting a medical education manuscript for publication.